2023
DOI: 10.1177/09564624221148622
|View full text |Cite
|
Sign up to set email alerts
|

The association between penile cancer and HIV infection: A literature review

Abstract: Penile cancer is a rare malignancy which HIV infection appears to increase the risk of. The magnitude of this risk and the pathogenesis remain unclear. A comprehensive review of the literature was undertaken using conventional search strategies. Twenty-four publications were identified by this methodology, of which nine were case reports and 15 were observational studies. These studies were highly heterogeneous, with varying study designs, populations, and objectives. The risk of penile cancer within HIV-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Furthermore, there's a faster progression from intraepithelial neoplasia to cancer (i.e., six years sooner) and increased cancer-specific mortality (i.e., four times higher). In addition, this review highlighted how coinfection by HPV is more frequent in this specific population, furtherly increasing the chance of developing penile cancer [18]. As estimated by Nunez et al [19], up to 18% (95% CI 14.3-22.1%) of patients affected by HIV are unaware of it, regardless of being men who have sex with men (MSM) or heterosexuals.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, there's a faster progression from intraepithelial neoplasia to cancer (i.e., six years sooner) and increased cancer-specific mortality (i.e., four times higher). In addition, this review highlighted how coinfection by HPV is more frequent in this specific population, furtherly increasing the chance of developing penile cancer [18]. As estimated by Nunez et al [19], up to 18% (95% CI 14.3-22.1%) of patients affected by HIV are unaware of it, regardless of being men who have sex with men (MSM) or heterosexuals.…”
Section: Discussionmentioning
confidence: 95%
“…Both HIV and hrHPV infections are associated with an increased risk of penile cancer development [ 6 , 10 , 20 , 21 ]. These infections may also have an effect on the penile cancer tumor microenvironment, which may affect prognosis and may require a different approach in use of immune therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies and case reports have reported that HIV infection is associated with a higher risk of progression from in-situ to invasive penile cancer [ 10 , 23 ]. In our study, there was no significant difference in the proportion of HIV positive individuals between those with advanced histological stage and those with early-stage disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation